Clarifying the Dairy Welfare Audit - Doyle, Kristina; McMullen, Brendan (Tufts Archival Research Center, 2019)
Clarifying the Dairy Welfare Audit. Doyle. This project intended to clarify the differences in-between the certification standards and scope of the four major on-farm dairy welfare-auditing systems (American Humane, Animal Welfare Approved, Certified Humane, and the National Dairy Farm Program) for the benefit and enlightenment of producers, retailers, and consumers alike. Audits were completed on five Connecticut dairy farms, revealing distinct differences between individual auditing programs. Results ought to encourage auditing programs to further educate constituents concerning the standards and scope of individual auditing systems.; Keywords: animal welfare, certification, welfare audit, dairy cattle; Thesis submitted for the MS in Animals and Public Policy degree.